VALIDITAS PENGEMBANGAN MULTIMEDIA INTERAKTIF ADOBE FLASH CS6 PADA PEMBELAJARAN PENDIDIKAN PANCASILA SEKOLAH DASAR - Noperi, Wenni Yulia; Reinita, Reinita (Muallimuna : Jurnal Madrasah Ibtidaiyah, 2024)
This research is based on the minimal use of technology-based media in the teaching and learning process in elementary schools, especially in Pancasila Education subjects. Teachers more often use surrounding objects and books as media, which makes students feel bored during learning. The aim of this research is to develop interactive multimedia using Adobe Flash CS6  for learning Pancasila Education, especially the Elements of the 1945 Constitution, in class V of SD Gugus 2, Nanggalo District, Padang City, which has high validity, practicality and effectiveness. This research is a type of research and development (Research & Development) by applying the ADDIE model which includes the stages of analysis, design, development, implementation and evaluation. The instruments used to collect data include validation, practicality and effectiveness instruments. Data was analyzed through validity, practicality and effectiveness analysis. The development of interactive multimedia Adobe Flash CS6  for learning Pancasila education in class V of SD Gugus 2, Nanggalo District, Padang City uses the ADDIE model. The results show that the average assessment of the three expert validators is 93.74%, which is categorized as very valid. The results show that any media is very suitable for use.